-4+[-3+(-5+9-2)]= quem comprovar a resposta ganha 30 pontos
Soluções para a tarefa
Respondido por
0
vamos lá...
![-4+[-3+(-5+9-2)]= \\ \\ -4+[-3+(-7+9)]= \\ \\ -4+[-3+(+2)]= \\ \\ -4+[-3+2]= \\ \\ -4+[-1]= \\ \\ -4-1=-5 -4+[-3+(-5+9-2)]= \\ \\ -4+[-3+(-7+9)]= \\ \\ -4+[-3+(+2)]= \\ \\ -4+[-3+2]= \\ \\ -4+[-1]= \\ \\ -4-1=-5](https://tex.z-dn.net/?f=-4%2B%5B-3%2B%28-5%2B9-2%29%5D%3D+%5C%5C++%5C%5C+-4%2B%5B-3%2B%28-7%2B9%29%5D%3D+%5C%5C++%5C%5C+-4%2B%5B-3%2B%28%2B2%29%5D%3D+%5C%5C++%5C%5C+-4%2B%5B-3%2B2%5D%3D+%5C%5C++%5C%5C+-4%2B%5B-1%5D%3D+%5C%5C++%5C%5C+-4-1%3D-5)
Respondido por
0
-4+[-3+(-5+9-2)]=
-4+[-3+(-5+7)]=
-4+[-3+2]=
-4+[-1]=
-4 - 1 =
-5
-4+[-3+(-5+7)]=
-4+[-3+2]=
-4+[-1]=
-4 - 1 =
-5
Perguntas interessantes
Geografia,
11 meses atrás
Matemática,
11 meses atrás
Informática,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Física,
1 ano atrás